Conservative Style, Liberal Production: Hemudu’s Binary System for Maintaining its Scapular Shovel Tradition in the Southern Yangzi Delta, 7000–6000 BP - Xie, Liye; Lun, Casey; Jiang, Leping; Sun, Guoping (Frontiers in Earth Science, 2021)
In the past two decades, archaeological studies of knowledge and skill transmission for pottery and lithic production in preindustrial societies have significantly improved our understanding of how technological traditions were transmitted and how the transmission processes influenced technological persistence and changes. However, case studies of craft transmission for osseous technology are rare despite their equal importance to pottery and lithic industries in preindustrial societies. Our research fills the gap by examining early Hemudu Culture’s (7000–6000 BP) scapular implements in the southern Yangzi Delta to understand the linkage between learning and maintaining the scapular shovel tradition in Hemudu’s socio-economic context. We first traced the history of scapular tools to the precedent Kuahuqiao Culture (8200–7000 BP), then used published experimental results to identify the product traits pertinent to craft learning and infer Hemudu scapular shovel blades’ learning and production patterns. Hemudu scapular shovels had a unique, complicated hafting style and an evidential raw material preference for old water buffalo scapulae. However, the blades’ morphological details and technical solutions varied significantly. In addition, most finished products display manufacturing mistakes resulting from crafters’ lacking skills, experience, and intervention. Practice pieces are rare compared to finished and used products. Although additional evidence implies that practice might have been more common than the studied sample suggested, it was carried out with less-than-ideal bones and insufficient for developing technical competency. We argue that the Hemudu societal norms for a scapular shovel applied only to the highly visible aspects of the implement. The shaft and ligatures could reduce the visibility of many manufacturing flaws on the shovel blade to reach the desired visual effect of the shovel. The shovel blades were made by household crafters emulating from an artifact or a memorized template but had insufficient training and practice in manufacturing. Communities of practice were minimal to nonexistent among the shovel makers; alternative mechanisms to maintain the technical norms or hold a high product standard were also lacking. Therefore, we concluded that the scapular shovels were less important as a technical implementation than a visual communicator of social identity. The binary system of conformist style and material preference mixed with loose quality control in the shovel blade production reveals that social conformity and the associated learning pattern are circumstantial and fluid even for a community’s iconic implement. Further research with other artifact types in Yangzi Delta would help shed light on whether similar learning patterns were applied besides the creation of scapular shovels.